The Development of Integrated Learning Model To Improve Language Skills at Arabic Language - Yogia Prihartini; Wahyudi Wahyudi (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2018)
This research has purpose to understand learning implementation condition at department of Arabic language, at FTK UIN STS Jambi, and trying to develop an integrated learning model for classroom learning teaching process in effort to increase Arabic scientific mastering. Object of study are students of Arabic language, at FTK UIN STS Jambi in 1 (first) and 3 (third) semester amount to 60 person.The method of this research is research and development method. The process performed in this research is to design and develop an integrated learning model in instructional field, after obtaining illustration and data from survey conducted to studied objects. Based on reality in field it showed that Arabic learning in departement of Arabic literature must still be improved. One methode is to developing the integrated learning model that can combine Arabic sciences into learning process, therefore it can be expected that students could appreciate Arabic sciences in comprehensive way. We hope this reaserch findings can be inputs for considering as an alternative in effort to develop an integrated learning model in Arabic instructional process.